2008
DOI: 10.1177/0095798408314142
|View full text |Cite
|
Sign up to set email alerts
|

Community Violence, Interpartner Conflict, Parenting, and Social Support as Predictors of the Social Competence of African American Preschool Children

Abstract: Adopting an ecological framework, this study examines the role of community violence exposure, interpartner conflict, positive parenting, and informal social support in predicting the social skills and behavior problems of low-income African American preschoolers. Participants were 184 African American mothers and female caregivers of Head Start children who completed study measures in a structured interview. Regression analyses revealed that greater community violence exposure predicted more internalizing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 44 publications
3
38
1
Order By: Relevance
“…Mothers who have been exposed to such violence are more likely to engage in higher levels of psychologically and physically aggressive parenting than are mothers without exposure, and aggressive parenting in turn increases child aggression. These findings corroborate the claim that parents are brokers of outside social contexts for young children who have little exposure to such contexts (Kohen et al, 2008;oravecz et al, 2008). The results also are consistent with theories and previous evidence that parents' violence exposure, often treated as a component of adverse community contexts or stressful life event scales, can impair parenting and child socioemotional development (Eamon, 2002;Kohen et al;Linares et al, 2001;oravecz et al).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Mothers who have been exposed to such violence are more likely to engage in higher levels of psychologically and physically aggressive parenting than are mothers without exposure, and aggressive parenting in turn increases child aggression. These findings corroborate the claim that parents are brokers of outside social contexts for young children who have little exposure to such contexts (Kohen et al, 2008;oravecz et al, 2008). The results also are consistent with theories and previous evidence that parents' violence exposure, often treated as a component of adverse community contexts or stressful life event scales, can impair parenting and child socioemotional development (Eamon, 2002;Kohen et al;Linares et al, 2001;oravecz et al).…”
Section: Discussionsupporting
confidence: 88%
“…Mothers' violence exposure as either a negative life event or a component shaping their images of disorganized social contexts can exert an impact on parenting (Kotchick et al, 2005;Linares et al, 2001;oravecz et al, 2008;Pinderhughes et al, 2001). For example, in a sample of parents living in poor neighborhoods, Pinderhughes et al found that perceptions of the prevalence of muggings, burglaries, assaults, and selling and using drugs in neighborhoods decreased parental warmth and parenting consistency.…”
Section: Effects Of Mothers' Violence Exposure On Parentingmentioning
confidence: 99%
“…Different studies have focused on different aspects of social support, and findings have been mixed. Although some researchers have found that higher levels of social support were related to fewer child behavior problems (Dodge et al, 1994; Leadbeater & Bishop, 1994), others have found no relationship (Oravecz, Koblinsky, & Randolph, 2008). Most of these studies have been cross-sectional and focused on European American or African American families.…”
Section: Social Supportmentioning
confidence: 99%
“…With reduced variability in the sensitivity construct, concordance in rank order between sensitive parenting and social skills may be more difficult to detect. In contrast, Oravecz, Koblinsky, and Randolph () reported a statistically significant association between sensitive parenting and children's social skills, but they also relied on parent report for all measures and cannot rule out the possibility of shared method variance partially accounting for their reported statistical associations.…”
Section: Discussionmentioning
confidence: 95%